Aspergilloma Mimicry of Lung Cancer: A Case Report - Bagus HS, Muhammad; Irvan Medison; Dewi Wahyu Fitrina; Dessy Mizarti (HM Publisher, 2024)
Background: Aspergilloma and lung cancer have similar risk factors, clinical features, and supporting features. Special supporting examinations are needed to rule out the differential diagnosis of aspergilloma. Case presentation: A 52-year-old male patient with coughing up blood and risk factors for smoking had a chest X-ray and computed tomography scan (CT scan) of the thorax and found a picture of a lung tumor. Bronchoscopy was carried out, and a bronchial lavage culture was carried out for the impression of Aspergillosis, given 1x150 mg of fluconazole for 6 months with improved clinical results and chest radiographs as well as negative sputum culture results. Conclusion: This patient showed the condition of aspergilloma mimicking lung cancer.